8=1z+6

Rewrite the equation as 1z+6=8.

1z+6=8

Multiply each term by z+6 and simplify.

Multiply each term in 1z+6=8 by z+6.

1z+6⋅(z+6)=8⋅(z+6)

Cancel the common factor of z+6.

Cancel the common factor.

1z+6⋅(z+6)=8⋅(z+6)

Rewrite the expression.

1=8⋅(z+6)

1=8⋅(z+6)

Simplify 8⋅(z+6).

Apply the distributive property.

1=8z+8⋅6

Multiply 8 by 6.

1=8z+48

1=8z+48

1=8z+48

Rewrite the equation as 8z+48=1.

8z+48=1

Move all terms not containing z to the right side of the equation.

Subtract 48 from both sides of the equation.

8z=1-48

Subtract 48 from 1.

8z=-47

8z=-47

Divide each term by 8 and simplify.

Divide each term in 8z=-47 by 8.

8z8=-478

Cancel the common factor of 8.

Cancel the common factor.

8z8=-478

Divide z by 1.

z=-478

z=-478

Move the negative in front of the fraction.

z=-478

z=-478

z=-478

The result can be shown in multiple forms.

Exact Form:

z=-478

Decimal Form:

z=-5.875

Mixed Number Form:

z=-578

Solve for z 8=1/(z+6)